A thick-walled sheet moulding compound automotive component: Manufacturing and performance. (January 2020) - Martulli, L.M.; Creemers, Thomas; Schöberl, Erich; Hale, Nicholas; Kerschbaum, Martin; Lomov, Stepan V.; Swolfs, Yentl
Abstract: Carbon Fibre Sheet Moulding Compounds (CF-SMCs) are lightweight materials very suitable for automotive parts. So far, their use was limited to thin components. This work presents a feasibility study on the compression moulding of a thick-walled SMC component, with a compound of randomly oriented chopped carbon fibre tapes. Bending tests were used to evaluate the effects of the manufacturing conditions on the mechanical performance. The choice of the charge pattern configuration played the paramount role in the final part performance, especially via the creation of weld surfaces, leading to a maximum strength difference of over 400%. The moulding temperature, pressure and cooling method showed no statistically significant influence on both strength and stiffness of the part. The results of this work can be used as a starting point in the design of manufacturing processes for thick SMC components.